INTEGRATING MULTICULTURALISM IN ISLAMIC COUNSELLING: A PHENOMENOLOGICAL ANALYSIS OF THE MUSLIM COMMUNITY IN MELAKA, MALAYSIA. - Pahlewi, Reza Mina; Slamet (UIN Sunan Kalijaga Yogyakarta, 2024)
Multiculturalism plays a significant role in shaping the dynamics of Islamic counseling, particularly in diverse communities such as the Muslim population in Melaka, Malaysia. This study explores the integration of multiculturalism in Islamic counseling through a phenomenological analysis of the lived experiences of Muslim individuals in Melaka. The research aims to examine how cultural diversity influences counseling practices, the challenges faced by Islamic counselors in a multicultural society, and the strategies employed to provide effective and culturally sensitive support. Using a qualitative phenomenological approach, data were collected through Focus Group Discussions (FGD), participatory observation, and document analysis. The findings indicate that cultural diversity within the Muslim community in Melaka significantly impacts counseling practices, requiring counselors to develop multicultural competencies alongside their Islamic counseling expertise. Participants highlighted the importance of integrating religious values with cultural awareness to ensure counseling approaches remain relevant and effective. Additionally, the study reveals that the interweaving of religious identity, traditional beliefs, and modern psychological practices poses both opportunities and challenges for Islamic counselors. This research contributes to the growing discourse on multicultural counseling by emphasizing the need for Islamic counselors to adopt a holistic approach that considers cultural, religious, and psychological dimensions. The study suggests that incorporating culturally adaptive strategies, fostering interfaith understanding, and collaborating with religious scholars can enhance the effectiveness of Islamic counseling in multicultural contexts. The findings underscore the necessity for structured training programs that equip counselors with both Islamic knowledge and multicultural sensitivity to better serve Malaysia’s diverse Muslim community.